The Impact of Temporal and Transformational Leadership on Innovation Performance: A Mediation Analysis of Self-Efficacy - Syamsul Hadi; Heppy Fitriana; Kusuma Chandra Kirana; Nanang Bagus Subekti; Ibukun Joyce Ogwu (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: Current business growth cannot be optimal if it is not accompanied by innovation performance. This study explores the relationship between innovation performance, temporal leadership, and transformational leadership involving an intervening variable of self-efficacy. Background Problems: The process of transforming management from manual to digital requires leaders to be temporal and transformational to support direct and indirect atmosphere of innovation performance through employees’ self-efficacy. Novelty: Temporal and transformational leadership are like two complementary currency coins in the process of changing from manual management to a digital system. Furthermore, this research has never been carried out, therefore validation is needed. Research Methods: The nonprobability sampling method of the study using saturated sampling involved 85 respondents of the employees of distributor company. The hypotheses were tested using SmartPLS. Finding/Results: The results showed that temporal leadership has a direct significant positive impact on innovation performance and self-efficacy. Additionally, transformational leadership also shows a direct significant positive impact on innovation performance and self-efficacy. This study argues that self-efficacy also shows a significant positive impact on innovation performance. In addition, self-efficacy intervened the impact of temporal and transformational leadership on innovation performance. Conclusion: Temporal and transformational leadership have a beneficial effect in increasing innovation performance and self-efficacy is proven to be a mediation. The practical implication is the need to strengthen leaders to maintain a positive attitude towards employee self-efficacy to carry out innovative performance.